Membangun Umat Antroposentris di Tengah Pandemi COVID-19 - Vini Hidayani; Doli Witro (Institut Agama Islam Negeri (IAIN) Keiri, 2021)
This study aims to determine the anthropocentric concept in the perspective of the Quran and the efforts/tips to build anthropocentric Muslims in the midst of a pandemic. The research question in this article is how is the anthropocentric concept in the Qur'an? And how to build an anthropocentric people in the midst of a pandemic? This article is library research. The research method used is a research method that uses qualitative data. The research materials come from books, scientific articles, research reports, internet websites, and so on related to the research theme, namely anthropocentric people and pandemics. Data collection techniques are by reading and understanding library materials that have been collected. Data analysis techniques used in data condensation, data presentation, and drawing conclusions. The results show that anthropocentric Islam is pro to humanity (humanist) without abandoning divine values ​​(theology). The idea of ​​building a pro-humanitarian community during the pandemic is an elaboration of the partnership between the government and local religious leaders, the collaboration of the Rukun Tetangga (RT) with residents, empowering crowdfunding applications, and fortifying themselves with healthy readings during social restrictions.